Ensuring physical activity of the population by involving citizens in sports tourism events - Gordeeva I.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess the opportunities for sports tourism provided by tourism operators in Yekaterinburg for various categories of citizens, as well as the preferences of specific age groups. Methods and structure of the study. The activities of 14 travel companies registered in Yekaterinburg and positioning themselves as domestic tourism operators providing services of one- and multi-day active tours designed for categories of citizens with different levels of physical fitness are considered. Results and conclusions. It is shown that currently tourism operators in Yekaterinburg offer a wide range of active tourism services designed for the population of all age categories and various levels of physical fitness. These events are in fairly high demand among the population of the region, giving citizens the opportunity, if they have the appropriate motivation, to provide themselves with the necessary level of physical activity in the form of weekend tours. It is shown that the preferences of different age categories in the field of active tourism of the population differ significantly, which must be taken into account by operators creating tour programs. At the same time, in terms of gender, the main consumers of tourism services are females; the predominance of any specific age groups of the population has not been identified. A high level of satisfaction with the provided tourist services is demonstrated equally by all age categories of the population: 56.7% of people of retirement age and 58.3% of hikers under the age of 35, which indicates the good organization of tourism activities in the region.